Pengembangan Media Augmented Reality (AR) Berbasis STEM untuk Meningkatkan Kemampuan Berpikir Kritis dalam Pembelajaran IPA - Syahrial A; Yulia Hasan; Wahyudi; Muhammad Zuhdi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to develop an Augmented Reality (AR)–based STEM learning media and examine its validity and effectiveness in improving students’ critical thinking skills in science learning. The research employed a 4D type Research and Development (R&D) model consisting of the Define, Design, Develop, and Disseminate stages, with expert validation, pretest–posttest assessments, N-Gain analysis, and teacher–student response questionnaires used as data collection instruments. The results and discussion indicate that the developed media is highly feasible, obtaining an average expert validation score of 3.5 and an Aiken’s V value of 0.83, and is effective in enhancing critical thinking skills, as shown by an increase in students’ scores from 57.5 to 94.4 and an N-Gain value of 0.38 categorized as moderate. The study concludes that the AR-based STEM media is valid, well-received, and sufficiently effective for science learning to support the improvement of students’ critical thinking skills.